Secular grace - Freibach-Heifetz, Dana. (Value Inquiry Book Series, 2017)
In Secular Grace Dana Freibach-Heifetz addresses the crisis of modernity, proposing an ethic of love based on a new philosophical concept of "secular grace\' as intersubjective relations. Anchored in secular humanism as well as within the existentialist tradition, yet recognizing their limitations, Secular Grace seeks to protrude them by means of dialogue with their other: Christianity. Inspired by a variety of intellectual roots from ancient Greece to post modernist thinkers - chiefly the deliberations of Buber and Levinas in the encounter with the other, and notions of gift and friendship - it offers a rich concept of Secular Grace . It furthermore examines the possibilities of grace towards the dead, self-grace and secular salvation.